Identification and characterization of multiple novel picornaviruses in fecal samples of bar-headed goose - Sun, Yijie; Wang, Yan; Ji, Li; Zhao, Qifan; Shen, Quan; Wang, Xiaochun; Liu, Yuwei; Ji, Likai; Yang, Shixing; Zhang, Wen (Frontiers in Microbiology, 2024)
The bar-headed goose (Anser indicus), one of the most well-known high-altitude birds, is renowned for its adaptation to high-altitude environments. Previous studies have shown that they can be infected with highly pathogenic avian influenza; however, there is currently limited research on other viruses in bar-headed geese. In this study, we identified seven novel picornaviruses in the fecal samples of bar-headed geese using viral metagenomics. Most of these picornaviruses were genetically different from other currently known viruses in the NCBI dataset. Among them, PICV4 was determined to be a new species belonging to the Anativirus genus, PICV5 and PICV13 were classified as novel species belonging to the Hepatovirus genus, and the remaining four picornaviruses (PICV1, PICV19, PICV21, and PICV22) were identified as part of the Megrivirus A species of the Megrivirus genus. Recombinant analysis indicates that PICV21 was a potential recombinant, and the major and minor parents were PICV1 and PICV22, respectively. The findings of this study increase our understanding of the diversity of picornaviruses in bar-headed geese and provide practical viral genome information for the prevention and treatment of potential viral diseases affecting this species.